Carson McCullers and Lillian Smith : The Intersections of Gender and Race in the Jim Crow South - González Groba, Constante (Journal of English Studies, 2008)
Carson McCullers and Lillian Smith openly rejected a false conception of loyalty to fantasies like southern tradition or white supremacy, a loyalty that veiled a persistent lack of self-analysis. They exposed the cracks in the South’s pretended “unity” and homogeneity and criticized the self-destructive resistance to acknowledge that, as a socially constructed category, race is linked to relations of power and anticipated the instability of racial categorization that would be underscored by historical and scientific research later in their century. These two southern women writers opposed the insistence of their culture on racial purity as vehemently as its demands for rigid sexual definition and its suppression of any deviant form of sexuality. The characters in their fiction are victims of a dichotomic culture that resists the acknowledgement that black and white have always been as inextricably linked as male and female. In Killers of the Dream and Strange Fruit, Lillian Smith showed the interactions of racial and sexual segregation, which she saw as parallel emblems of the South’s cultural schizophrenia. She was one of the first to detect the psychosexual damage inflicted on southern women by the racial discourse, and established a most interesting parallel between the segregated parts of the female body and the segregated spaces of any southern locality. Like any system of differentiation, segregation shapes those it privileges as well as those it oppresses. Excluded from the white parameters of virtue and even from the condition of womanhood, the black woman’s body became the sexual prey of the white man who could not demand sexual satisfaction from his “pure” wife. The culture of segregation privileged the white woman but it also made her powerless; the very conventions which “protected” her deprived her of contact with physicality and locked her into bodilessness.